O campo termo-higrométrico intra-urbano e a formação de ilhas de calor e de frescor urbanas em Santa Maria/RS - Costa, Eduino Rodrigues da (2009)
Urbanization and the changes imposed by man disturb the complex natural system, modifying the elements and characteristics of climate on a local scale. Considering the influence of urbanization as derived from the fact that the local climate and responsible for the generation of an urban environment specifically, this work was to analyze the field thermo-hygrometric and the formation of heat islands and urban cool in Santa Maria RS (Rio Grande do Sul, State of Southern of Brazil), relating these variables geourbans and geoecologycs in the study area. To accomplish this work was used the methodology of the transects, consisting of mobile collections in points pre-established. It was established two transects for data collection of temperature and relative humidity of the atmospheric air: one has the direction more or less in a north/northwest-south/southeast (NNW-SSE), linking Street Sete de Setembro , in Neighborhood Perpétuo Socorro , the end Fernando Ferrari Avenue in Neighborhood Nossa Senhora de Lourdes and the other in the east/northeastwest/southwest (WSW-ENE), linking the Street Major Duarte to get Street Venâncio Aires near the Arroio Cadena at Central portion of the Santa Maria City. The data were collected on days August 14, 2008 and January 06, 2009, the area was under the weather for the South Atlantic Polar Mass in winter time and the Old Polar Mass or modified in the summer, respectively. Were made cotte measures at five different times (9, 12, 15h, 18h and 21h), in order to verify the responses of thermal and humidity from the points pre-established and distributed along the transects, totaling 13 points of measures along the transect 1 (NNWSSE) and 15 in the transect 2 (ENE-WSW). Armed with the data of temperature and humidity, were made cartograms of the field thermo-hygrometric. For this application was used the Software Surfer for Windows 8.0. In the preparation of cartograms of the thermal field were established color scales to represent the values of temperature, so the cool colors were associated with lower temperatures and the warm colors at higher temperatures. Cartograms of hygrometric field values were represented in the cartogram using a variation of blue scale, so the lighter blue was used to represent the values of lower humidity and dark blue for higher values. The results highlight that the hygrometric and thermal fields of the coverage area of the transects, both on the day of collection in the field of Mass Polar Atlantic in winter time and in the field of Old Polar Mass or modified in the summer, need to move apparent daily sun exposure of the slopes and to solar radiation. By analyzing the thermal field of January 06, 2009 in five hours of collection, it became clear the migratory movements of the heat islands of the eastern slope, during the morning, to the slopes facing the north and west quadrant, during periods of midday and afternoon. The weather conditions that occurred on January 06, 2009 (summer), with clear skies, calm winds and a light with high incidence of solar radiation on the surface, favored the formation of heat islands and freshness of magnitude rating, strong and very strong. Was verified the thermal contrast between the center and periphery of the study area.